2022
DOI: 10.1021/acsami.2c04734
|View full text |Cite
|
Sign up to set email alerts
|

ZnFe2O4–Ni5P4 Mott–Schottky Heterojunctions to Promote Kinetics for Advanced Li–S Batteries

Abstract: The practical progress of lithium−sulfur batteries is hindered by the serious shuttle effect and the slow oxidation− reduction kinetics of polysulfides. Herein, the ZnFe 2 O 4 −Ni 5 P 4 Mott−Schottky heterojunction material is prepared to address these issues. Benefitting from a self-generated built-in electric field, ZnFe 2 O 4 −Ni 5 P 4 as an efficient bidirectional catalysis regulates the charge distribution at the interface and accelerates electron transfer. Meanwhile, the synergy of the strong adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…The active sites of transition metal catalysts usually have an affinity for polysulfides, which results in a large amount of Li 2 S accumulating and reducing the oxidation kinetics during charging. This can be remedied through, in addition to the common structure modulation, the construction of heterogeneous structures, which can also enhance the bidirectional redox kinetics of Li–S batteies. In contrast to individual TMCs, the heterogeneous structures designed by interface engineering combine the advantages of different materials to create synergistic effects that result in good physicochemical properties. Recently, an increasing number of researchers found that the heterostructures could accelerate charge transfer and promote the bidirectional sulfur reaction kinetics to significantly improve the electrochemical performance of Li–S batteries. Table shows the electrochemical performance of heterostructures as the sulfur host/separator modifier in Li–S batteries.…”
Section: Tmcs In Li–s Batteriesmentioning
confidence: 99%
“…The active sites of transition metal catalysts usually have an affinity for polysulfides, which results in a large amount of Li 2 S accumulating and reducing the oxidation kinetics during charging. This can be remedied through, in addition to the common structure modulation, the construction of heterogeneous structures, which can also enhance the bidirectional redox kinetics of Li–S batteies. In contrast to individual TMCs, the heterogeneous structures designed by interface engineering combine the advantages of different materials to create synergistic effects that result in good physicochemical properties. Recently, an increasing number of researchers found that the heterostructures could accelerate charge transfer and promote the bidirectional sulfur reaction kinetics to significantly improve the electrochemical performance of Li–S batteries. Table shows the electrochemical performance of heterostructures as the sulfur host/separator modifier in Li–S batteries.…”
Section: Tmcs In Li–s Batteriesmentioning
confidence: 99%
“…15,16 Interface engineering can fully combine the advantages of both components, and the strong interactions between interfaces enable manipulation of the surface electronic structure and accelerate electron transfer, opening a way to enhance the intrinsic conductivity and electrocatalytic activity of semiconductors. 17,18 Indeed, studies have shown that coupling p-type semiconductors with n-type semiconductors to form p-n heterojunction as catalytic materials (p-Co 3 O 4 /n-TiO 2 -HPs, NiO-Co 9 S 8 /rGO) considerably improves the performance of LSBs, and theoretical and experimental results indicate that the formed built-in electric eld at the p-n heterojunction interface can greatly enhance the adsorption of LiPSs and reaction kinetics of polysulde reduction and Li 2 S oxidation. 19,20 Therefore, it is feasible to increase the electroactivity and conductivity of MoS 2 by reasonably constructing p-n heterojunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al prepared the TiO 2 –TiN heterostructure and loaded it onto graphene, and LiPSs can realize a rapid “adsorption–diffusion–transformation” process at the interface, which greatly restrained the shuttle effect and upgraded the cycle performance . More recently, many burgeoning heterostructures, such as CoS 2 –Fe 7 S 8 , WS 2 –WO 3 , Co 9 S 8 –MoS 2 , ZnS–FeS, Co 3 S 4 /MnS, ZnFe 2 O 4 –Ni 5 P 4 , and CoMoS 3 –CoS, have been advanced into Li–S batteries as sulfur hosts or intermediate layer materials. Therefore, a reasonable design of the heterostructure is expected to be the most useful route for solving the shuttle effect of Li–S batteries based on the combination of chemical adsorption and catalytic conversion.…”
Section: Introductionmentioning
confidence: 99%
“…WS 2 −WO 3 ,22 Co 9 S 8 −MoS 2 ,23 ZnS−FeS,24 Co 3 S 4 /MnS,25 ZnFe 2 O 4 −Ni 5 P 4 ,26 and CoMoS 3 − CoS,27 have been advanced into Li−S batteries as sulfur hosts or intermediate layer materials. Therefore, a reasonable design of the heterostructure is expected to be the most useful route for solving the shuttle effect of Li−S batteries based on the combination of chemical adsorption and catalytic conversion.…”
mentioning
confidence: 99%